Applied transport economics policy, management & decision making - Cole, Stuart (Kogan Page Limited, 2005)
Revised and updated to cover developments and thinking in transport economics, the book examines the application of economics techniques first, to commercial transport operations, second, to public policy issues and third, to the role of transport in its wider economic context